Kriya practice from the perspective of ecofemism - Wahyono (Cogent Arts & Humanities)
Environmental protection is one of the most serious issues that mankind confronts, and humans, from an anthropocentric perspective, are put at the center of managing nature. Grounded in a patriarchal view, it allows humans to control, exploit, and maximize the use of nature without regard for the ramifications for human civilization’s future. Criticizing this destructive practice, the emergence of ecofeminism based on the concept of environmental management that supports the position of women. Ecofeminism begins with the perception of feminism, in which the unequal position of women in society is subject to being compared to that of men. This study shows how the concept of ecofeminism can penetrate the public consciousness, especially among women, through the role of art, the kriya. Using the library research method, this article analyzes the notion of ecofeminism, attempting to demonstrate not just how women and nature are related but also the way humans attempt to rule the planet from an anthropocentric perspective. Saving women, nature, and the environment is vital from the standpoint of ecofeminism since it can indirectly save all lives. Moreover, in the social context, kriya’s work does not end in its concrete form. Her kriya works also help raise awareness of the cultural community, especially among women. The artist must fight against this condition of inequality by avoiding the tendency to carry out social conformity and continuing to support the persecuted group. This can be accomplished by employing kriya as a vehicle for children and women to internalize ecofeminist ideals.